Environmental DNA (eDNA) for monitoring marine mammals: Challenges and opportunities - Suarez-Bregua, Paula; Álvarez-González, Miguel; Parsons, Kim M.; Rotllant, Josep; Pierce, Graham J.; Saavedra, Camilo (Frontiers in Marine Science, 2022)
Monitoring marine mammal populations is essential to permit assessment of population status as required by both national and international legislation. Traditional monitoring methods often rely on visual and/or acoustic detections from vessels and aircraft, but limitations including cost, errors in the detection of some species and dependence on taxonomic expertise, as well as good weather and visibility conditions often limit the temporal and spatial scale of effective, long-term monitoring programs. In recent years, environmental DNA (eDNA) has emerged as a revolutionary tool for cost-effective, sensitive, non-invasive species monitoring in both terrestrial and aquatic realms. eDNA is a rapidly developing field and a growing number of studies have successfully implemented this approach for the detection and identification of marine mammals. Here, we review 21 studies published between 2012 and 2021 that employed eDNA for marine mammal monitoring including single species detection, biodiversity assessment and genetic characterization. eDNA has successfully been used to infer species presence (especially useful for rare, elusive or threatened species) and to characterize the population genetic structure, although additional research is needed to support the interpretation of non-detections. Finally, we discuss the challenges and the opportunities that eDNA could bring to marine mammal monitoring as a complementary tool to support visual and acoustic methods.